Effect of Using Fenugreek, Parsley and Sweet Basil Seeds as Feed Additives on the Performance of Broiler Chickens - Abbas, Rabia J. (International Journal of Poultry Science, 2010)
A research study was conducted to find the effect of Fenugreek (Trigonella Foenum-Graecum L.), parsley (Petroselium sativam L.) and Sweet Basil (Ocimum basilicum L.) seeds as natural feed additives on broiler performance. A total of 120 day-old chicks were reared for 42 days. Feed and water were provided ad libitum. Chicks were divided into four treatments (30 birds each). Each treatment contained three replicates of 10 birds. Each treatment was fed on one of the following experimental diets:1) Control diets (without supplementation). 2) Control diets supplied with Fenugreek at 3 g/kg of the diet. 3) Control diets supplied with parsley at 3 g/kg of the diet. 4) Control diets supplied with Basil at 3 g/kg of the diet. Chicks fed basil diets had significantly (p<0.05) heaviest body weight than those fed the control and fenugreek diets. Carcass characteristics had no significant differences. Significant reduction occurred in serum cholesterol as compared to control diets. It would suggested that the supplementation of broiler chicks diets with (3 g/kg) basil or parsley seeds improved productive performance.